Handbook of sustainable luxury textiles and fashion. - Gardetti, Miguel Ángel; Muthu, Subramanian Senthilkannan (Environmental footprints and eco-design of products and processes., 2016)
The second volume of handbook explores different dimensions of the sustainable luxury textiles and fashion, broadly based on the following topics: Sustainable luxury Luxury and consumption Luxury, innovation and design potential Luxury and entrepreneurship Sustainable Luxury Management.